JOURNEY TO MANAGEMENT ORGANIZATION INSIGHT ISSUES AND CHALLENGES - Badarudin Mat Isa; Anuar Alias (2014)
Our aim of writing is just to relate our different generation management exposures, experiences and to minimize gaps. On the other hand, we feel that we should not be too skeptical about this feeling. These philosophical words inspired us to continue our idea of writing this book with the sincere hope that it could be of use to some of the up-coming managers in whatever organization they may serve. It is not for glory or recognition, but based on our sincerity with the hope that it could be of guidance to some people, and therefore we treat this book as charitable activities, if it could really be resourceful to others. As many people observed, management and administration are usually placed on the top of the hierarchy of any organization. Most people think that managing is very difficult, but it could be made simple if we keep things simple, logical, practical and most importantly we are willing and committed to lead the organization. Manager must make such decisions as practical, logical, simple and timely as possible. This book has eleven chapters from management concepts to managing conflicts in organization.